Dietary Salba (Salvia hispanica L.) ameliorates the adipose tissue dysfunction of dyslipemic insulin-resistant rats through mechanisms involving oxidative stress, inflammatory cytokines and peroxisome proliferator-activated receptor γ - Ferreira Cordoneda, Maria del Rosario (2018)
Purpose: Rats fed a long-term sucrose-rich diet (SRD) developed adipose tissue dysfunction. In the adipose tissue of these SRD-fed rats, the present study analyzed the possible beneficial effects of dietary Salba (chia) seeds in improving or reversing the depletion of antioxidant defenses, changes in pro-inflammatory cytokines and ROS production. Methods: Wistar rats were fed a SRD for 3 months. After that, half of the animals continued with the SRD until month 6, while in the other half, corn oil was replaced by chia seeds for 3 months (SRD + chia). A reference group consumed a control diet all the time. Results: Compared with the SRD-fed rats, the animals fed a SRD + chia showed a reduction in epididymal fat pad weight; the activities of antioxidant enzymes CAT, SOD and GPx returned to control values, while GR significantly improved; mRNA GPx increased, and both mRNA SOD and the redox state of glutathione returned to control values; a significant increase in the expression of Nrf2 was recorded. These results were accompanied by a decrease in XO activity and ROS contents as well as plasma IL-6 and TNF-α levels. Chia seeds reversed the decrease in PPARγ protein mass level and increased the n-3/n-6 fatty acids ratio of membrane phospholipids. Besides, dyslipidemia and insulin sensitivity were normalized. Conclusion: This study provides new information concerning some mechanisms related to the beneficial effects of dietary chia seeds in reversing adipose tissue oxidative stress and improving the adipose tissue dysfunction induced by a SRD.